Relationship between rate perceived exertion and anthropometric and physical changes in wheelchair basketball - Aitor Iturricastillo Urteaga; Maite Fuentes Azpiroz; Miren Lizundia Cortazar; Cristina Granados Domínguez (Federación Extremeña de Balonmano; University of Extremadura, 2022)
The objective of the study was to describe the association between the internal load and changes in anthropometric characteristics and physical condition during a pre-season a wheelchair basketball team (WB players). Eleven male wheelchair basketball players participated in this study and performed a test battery (anthropometry, 5 and 20m sprint with and without ball, t-test, pick-up, hand grip, maximal pass, the throwing of medicine ball and intermittent recovery resistance test (Yo-Yo 10m) before (Pretest) and after (Posttest) the preseason. Significant differences were observed in the perimeter of the arm relaxed and flexed, in the sprint of 5m without ball, in the sprint of 20m with ball, in the t-test, in the throwing of medicine ball, in the distance covered and in the concentration of capillary blood lactate between the pretest and the posttest. In addition, associations were observed in the percentage of change between the different physical condition tests (5m sprint with and without ball, 20m sprint with ball and pick-up) and the internal load. The results obtained in this study show that the training made twice a week during the preseason could produce positive changes in physical performance in WB players.